Bending and free vibration analysis of functionally graded plates using new eight-unknown shear deformation theory by finite element method - Long, Nguyen Van; Quoc, Tran Huu; Tu, Tran Minh (Vietnam Journal of Science and Technology, 2016)
In this paper, a new eight-unknown shear deformation theory is developed for bending and free vibration analysis of functionally graded plates by finite element method. The theory based on full twelve-unknown higher order shear deformation theory, simultaneously satisfy zeros transverse stresses at top and bottom surface of FG plates. A four-node rectangular element with sixteen degrees of freedom per node is used. Poisson’s ratios, Young’s moduli and material densities vary continuously in thickness direction according to the volume fraction of constituents which is modeled as power law functions. Results are verified with available results in the literature. Parametric studies are performed for different power law index, side-to-thickness ratios.